A Monumental Astrolabe Made for Shāh Jahān and Later Reworked with Sanskrit Legends - Sarma, Sreeramula Rajeswara (Medieval encounters, 2017)
When the astrolabe was introduced in India around the eleventh century, it was received with great enthusiasm. While the Muslims continued the Middle Eastern tradition of the study and manufacture of the astrolabe, the Hindus and Jains, who did not read Arabic, composed manuals on the astrolabe in Sanskrit, produced astrolabes with Sanskrit inscriptions, and also occasionally added Sanskrit legends to the Arabic/Persian astrolabes. A very large astrolabe, which is thoroughly reworked in this manner with Sanskrit legends, is the subject of this paper. During the process of reworking the name of the original maker of the astrolabe, the date of its manufacture, and other such details got effaced. But on the basis of the internal evidence, it will be argued that the astrolabe was originally produced between 1648 and 1658 by Ḍiyāʾ al-Dīn Muḥammad of Lahore for the Mughal Emperor Shāh Jahān. The study continues with a technical description of the components of the astrolabe, in which an attempt will be made to record all the original Arabic inscriptions and the subsequent engravings in Sanskrit.